A Systems-Based- Interdisciplinary Model For Chronic Disease Care: Integrating Radiological Assessment, Clinical Nursing Oversight, And Social Work Intervention To Advance Patient Screening, Monitoring, And Psychosocial Wellbeing (The Review of Diabetic Studies, 2024)
The escalating prevalence of chronic diseases, epitomized by heart failure (HF), represents the preeminent challenge to global healthcare sustainability in the 21st century. As populations age and survival rates from acute cardiac events improve, healthcare systems face a "paradox of success": a rising tide of complex, multimorbid patients who require continuous, rather than episodic, management. This systematic review critiques the prevailing biomedical model—characterized by fragmented, reactive care—and proposes a comprehensive, systems-based interdisciplinary model. By synthesizing global health data, randomized controlled trials, and observational studies, this report evaluates the integration of three critical domains: Radiological Assessment, specifically the democratization of point-of-care ultrasound (POCUS) and the strategic "visible" radiologist; Clinical Nursing Oversight, empowered through autonomous titration protocols and nurse-led ambulatory units; and Social Work Intervention, which operationalizes the management of social determinants of health (SDoH).The analysis reveals that while pharmacological advances such as Angiotensin Receptor-Neprilysin Inhibitors (ARNI) and Sodium-Glucose Cotransporter-2 (SGLT2) inhibitors are pivotal, their real-world efficacy is severely attenuated by systemic fragmentation. The proposed triad creates a synergistic safety net: radiological precision guides nursing vigilance, while social work intervention secures the psychosocial foundation necessary for adherence and stability. Data indicates that this integrated approach significantly reduces hospital readmissions (by up to 89% in specific cohorts), lowers global economic burdens (estimated at $284 billion annually), and improves patient quality of life. This report delineates the mechanisms of this integration, offering a roadmap for healthcare administrators and policymakers to transition from fee-for-service fragmentation to value-based, holistic chronic care.